Analisis Pengembangan Petani Teh Bedana Berbasis Zakat Produktif Pasca Covid 19 (Studi Kasus Pada UMKM Bedana Maju Desa Bedana Kab. Banjarnegara) - Ahmad Irfanudin; Muhammad Irfan Mahyuddin; Amirus Shodiq (Indonesian Journal of Islamic Economics and Business, 2026)
This study aims to analyze the development of tea farmers in Bedana Village through the utilization of productive zakat after the Covid-19 pandemic, with a focus on improving production quality, strengthening the value chain, and its impact on farmers' economic independence. The method used was a qualitative approach with field research. Data were obtained through interviews, observations, and documentation with members of the Bedana Maju UMKM Group and related parties. The results indicate that the implementation of productive zakat through the assistance of tea processing technology, such as rotary dryers and other supporting equipment, can improve production efficiency, product quality, and processing capacity. Furthermore, the value chain has strengthened, marked by a shift in the role of farmers from sellers of raw materials to producers of value-added processed tea. The impact of this program not only increases farmers' incomes but also strengthens social institutions, creates job opportunities, and encourages community economic independence. Thus, productive zakat has proven effective as an instrument for economic empowerment and post-pandemic recovery based on the agricultural sector.